Radio drama with Shaun Mac Loughlin (North Ryde, NSW. : Australian Film Television & Radio School, 1987)
An entertaining and interesting look at the process of radio drama production through master classes led by Shaun MacLoughlin, a British director of over two hundred BBC radio plays
Keywords: Radio plays -- Production and direction